NEUROACCOUNTING DAN PENGAMBILAN KEPUTUSAN KEUANGAN: BUKTI EMPIRIS PADA UMKM KULINER DI JAWA TIMUR : NEUROACCOUNTING AND FINANCIAL DECISION MAKING: EMPIRICAL EVIDENCE IN CULINARY MSMES IN EAST JAVA - Haryana, Ratih Dewi Titisari; Prayogi, Gusti Dian (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study explores the application of neuroaccounting in understanding financial decision-making among culinary MSMEs in East Java. Neuroaccounting offers comprehensive insights by examining how cognitive literacy, emotional intelligence, and financial literacy influence decision-making, with business experience tested as a moderating factor. Using a quantitative design, cluster random sampling was applied to select six regencies with high MSME growth. A total of 407 culinary MSMEs participated, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) and Moderated Regression Analysis (MRA). The results show that cognitive literacy, emotional intelligence, and financial literacy significantly affect financial decision-making, while business experience strengthens these relationships. These findings indicate that neuroaccounting can enhance MSMEs’ ability to make better financial decisions by integrating cognitive, emotional, and financial competencies with practical experience. Theoretically, this study extends neuroaccounting by positioning literacy and emotional intelligence as core drivers of MSME decision-making, moderated by business experience. Practically, it offers guidance for policymakers, educators, and practitioners to develop targeted training and experience-based programs that improve financial capabilities and ensure business ustainability